A K-band switched-line phase shifter using novel low-voltage low-loss RF-MEMS switch - Ma, Li-Ya; Soin, Norhayati; Nordin, Anis Nurashikin (IEEE, 2017)
—A low-voltage low-loss K-band 3-bit MEMS switched-line phase shifter is presented in this work. The phase shifter is constructed by novel shunt capacitive RF-MEMS switches and coplanar waveguide lines on a high-resistivity silicon substrate. A low-voltage RF-MEMS switch (pull-in voltage = 3.04V) is employed and exhibits good RF characteristics by using T-match technique where its insertion loss and isolation is - 0.1291dB and -28.75dB, respectively at frequency of 20GHz. The 3-bit MEMS phase shifter is assembled by three single-bit units (namely, 45°-bit, 90°-bit and 180°-bit) of switched-line structures; the average phase error and average insertion loss is 0.2445° and -2.447dB, respectively, at 20GHz; its return loss is better than 10dB at a wideband frequency range of up to 20GHz. The whole design area is 6mm*4mm